Sengketa Pengelolaan Lahan Lanudal Juanda Tahun 1973–1998 - Muhammad Mahendra Januar; Wisnu W (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Juanda Naval Air Base (Lanudal Juanda) was originally developed as an operational base for the Indonesian Navy's aviation forces, but over time it was also utilized as a civil airport through a civil enclave arrangement. This functional transformation created a shared-authority structure between the Indonesian Navy (TNI AL) and Perum Angkasa Pura I, which gradually developed into a land management dispute during the period 1973–1998. This study aims to analyze the background, causal factors, dynamics, and settlement efforts related to this dispute. The research employs the historical method, consisting of heuristics, source criticism, interpretation, and historiography. Data were obtained from government regulations, institutional archives, newspaper reports, interviews, and secondary literature, and were analyzed using conflict theory. The findings show that the dispute stemmed from divergent interpretations of asset-ownership status following the transfer of civil-aviation management authority, from the growing operational needs of Bandara Juanda as an international airport, and from differing institutional interests between the Navy, which prioritized defense functions, and Angkasa Pura I, which prioritized public service and infrastructure development. Settlement efforts were pursued mainly through deliberation, negotiation, and inter-institutional coordination, but had not produced a comprehensive agreement by the end of the study period. The study concludes that the Juanda land management dispute reflects the broader dynamics of civil–military relations in Indonesia's management of strategically important state assets.